A descriptive framework for additive remanufacturing systems. (1st December 2014) - Rickli, Jeremy L.; Dasgupta, Ashish K.; Dinda, Guru P.
Additive manufacturing, which is envisioned to transform manufacturing by offering extraordinary levels of customisation and agility, has also been shown to be transformative to remanufacturing. High value end–of–life cores are able to be restored to original equipment manufacturer specifications for a fraction of the price of new production using advanced condition assessment and material deposition technologies. However, this capability is only realised if advanced technologies work in harmony to assess, reprocess, and inspect end–of–life cores. In this paper, we describe a framework for remanufacturing systems that aims to take advantage of additive manufacturing processes to remanufacture end–of–life cores. The presented framework is divided into three critical stages; condition assessment and digitisation, material deposition, and reprocessing and final inspection. Technology advancements and current challenges are discussed for each stage and a case study is presented to further illustrate the three stages of the additive remanufacturing system framework.